2008
DOI: 10.1007/s00442-008-1233-5
|View full text |Cite
|
Sign up to set email alerts
|

The effect of climate on masting in the European larch and on its specific seed predators

Abstract: Masting is the intermittent production of large seed crops by a population of plants. Two main hypotheses have been proposed to explain masting. Variations in seed crop may result from stochastic climate factors (temperature, rainfall, etc.), and/or masting may be a plant evolutionary strategy to avoid specific seed predators. To determine the effect of climate on the annual pattern of cone production in the European larch (Larix decidua), we analyzed larch cone production from 1975 to 2005 at 20 sites in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(45 citation statements)
references
References 38 publications
0
39
0
1
Order By: Relevance
“…This phenomenon has been reported for many tree and shrub species and a variety of ecosystems (Herrera et al 1998;Koenig and Knops 2000;Schauber et al 2002;Suzuki et al 2005;Lázaro et al 2006;Poncet et al 2009). Many studies have shown that masting is caused by an interaction between abiotic and biotic factors (Mduma et al 2007).…”
Section: Cone and Seed Productionmentioning
confidence: 93%
“…This phenomenon has been reported for many tree and shrub species and a variety of ecosystems (Herrera et al 1998;Koenig and Knops 2000;Schauber et al 2002;Suzuki et al 2005;Lázaro et al 2006;Poncet et al 2009). Many studies have shown that masting is caused by an interaction between abiotic and biotic factors (Mduma et al 2007).…”
Section: Cone and Seed Productionmentioning
confidence: 93%
“…This supports the predator satiation hypothesis (Janzen 1974;Salisbury 1942), which is expected in low diversity plant communities where masting occurs (Nilsson and Wastljung 1987;Homma et al 1999) and where predation predominates over animal-mediated dispersal (Hulme and Hunt 1999;Vander Wall 2002), as is clearly the case in our study. A predator control based on these two mechanisms has been identified in alpine ecosystems, enhancing fitness in European larch (Poncet et al 2009), which suggests that the described pattern may be common, at least in limiting environments. In the case of P. pinea, the 'safe' period resulting from this strategy and the time where germination is possible (early fall) overlap (Manso et al 2013a, b).…”
Section: Seed Removal Patternsmentioning
confidence: 96%
“…Several studies have demonstrated different aspects of inter-population variation in seed production and seed mass, including climatic factors (Murray et al 2004;Poncet et al 2009), altitudinal gradients (Totland and Birks 1996;Pluess et al 2005), latitudinal variation (Winn and Gross 1993;Garcia et al 2000;Moles and Westoby 2003;Murray et al 2004;Moles et al 2007;De Frenne et al 2009), soil fertility (Wolfe 1995;Tungate et al 2002) and differences in habitat type (Endels et al 2004;Goulart et al 2006).…”
Section: Introductionmentioning
confidence: 99%